Given the following expression grammar for simple arithematic  expression with operator + and *.

E→ E+T  | T

T  → T+F  | F

F → (E)  | a

Remove the left recursion from this grammar then simplify and convert to CNF.

 

  • Answered by oriattic
  • 1 Comments
  • 1 year ago

This answer is restricted. Please login to view the answer of this question.

Login Now
Leave your Answer:

Click here to submit your answer.

s
Subscribe
Notify of
1 Comment
Oldest
Newest Most Voted
Inline Feedbacks
View all comments